EKSTRAK ETANOL RIMPANG LEMPUYANG GAJAH (Zingiber zerumbet (L.) J. E. Smith) SEBAGAI LARVASIDA TERHADAP LARVA INSTAR III-IV Culex quinquefasciatus - , YACOBUS CH. PRASETYO, dr. Tri Baskoro Tunggul Satoto, M.Sc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. Culex quinquefasciatus is the main vector of bancrofti filariasis in South East Asia. Interrupting the life cycle of the vector is main strategy to reduce the incidence of filariasis. The breeding of the mosquito is eradicated by larvicide, especially synthetic larvicide. This causes problems especially when synthetic larvicide is applied uncontrollably. The problems consist of vector resistance and environmental pollution. Therefore, it is essential to search for alternative larvicide, for instance Zingiber zerumbet as natural larvicide. Objectives. To explore larvicidal effect of Zingiber zerumbet roots with ethanol extract. To find out LC50 and LC90 of the extract against 3rd/4th instar larvae of Culex quinquefasciatus. To find out the relation between variety of the extract dose and larvae mortality. Methods. This research is quasi experimental study using WHO 2005 guidance. 3rd/4th instar larvae divided into 6 treatment groups and 1 control group. Each group contains 10 larvae with 3 times replication in 100 ml solution. Larvae mortality was counted after 24 hours of exposure and the data was analyzed using probit analysis. Result. LC50 and LC90 values were 72.49931 ppm and 154.3412 ppm. The probit regression line obtained is Y = -2.27 + 3.91X. Conclusion. Ethanol extract of Zingiber zerumbet roots has larvacidal activity against 3rd/4th instar of Culex quinquefasciatus larvae. LC50 and LC90 values were 72.49931 ppm and 154.3412 ppm. The increasing dose of the extract increases larvae mortality.